Some observations on erosion mechanisms of EB PVD TBCS - Wellman, R. G.; Nicholls, John R. (Elsevier Science B.V., Amsterdam., 2000)
Following the successful application of electron beam (EB) physical vapour deposition (PVD) thermal barrier coatings (TBCs) to moving parts of turbine engines, the erosion resistance of these coatings has been of interest among researchers. However, although there are a number of papers on the erosion rate of these coatings, little has been reported on their erosion mechanism. This paper provides observations on the erosion damage of EB PVD TBCs and discusses the type of damage caused by erosion, as well as proposing a possible mechanism of erosion. The aim of the project as a whole was to model the erosion of EB PVD TBCs, but before modelling could begin, it was necessary to determine the erosion mechanism of these coatings. It was found that in all cases examined, the erosion of the coatings proceeds through the accumulation of damage in the form of horizontal cracks in the columns of the coating and subsequent removal of the fractured sections. Since it appears as though the contact radius is important in the erosion process, the effect of varying the elastic properties of the erodent and the target on the contact radius was assessed.
Keywords: Erosion mechanisms; Thermal barrier coatings